A) 3(x+3)=2(x+4)+x+1=
b) 4(3x+2)+5(2x+3)=(2x+13)=
c) 4(x-2)-2(x-4)5(x+1)-3x=
d) 2(x-4)=2(2x-1)+6(x+1)=
e) 0,2x+0,3=1,3
f) 0,2x+0,3=1,3
g) 0,83x+0,82=0,23x+1,52=
h) 0,6x+2(0,1x-0,1)=0,2(x+1)=
i) 0,15(2x+4)=2(1,3+0,3x)-0,6=
j) 0,1(x+1)-0,05(3x-10)=0,4-0,35x

Wszystkim z góry dziekuje!!!

2

Odpowiedzi

2010-02-26T17:30:54+01:00
A) 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x=8+1-9
x=0
b) 4(3x+2)+5(2x+3)=(2x+13)
12x+8+10x+15=2x+13
12x+10x-2x=13-8-15
20x=-10/:20
x=-0,5
c) 4(x-2)-2(x-4)5(x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0x=5
d) 2(x-4)=2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x-4x-6x=-2+6+8
-8x=12/:(-8)
x=-1,5
e) 0,2x+0,3=1,3
0,2x=1,3-0,3
0,2x=1/:0,2
x=5
f) 0,2x+0,3=1,3-to jest takie same jak punkt e ;]
g) 0,83x+0,82=0,23x+1,52
0,83x-0,23x=1,52-0,82
0,6x=0,7/:0,6
x=1,1(6)


2010-02-26T17:40:01+01:00
A) 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x+x=8+1-9
2x=0/:2
x=0
b) 4(3x+2)+5(2x+3)=(2x+13)
12x+8+10x+15=2x+13
12x+10x-2x=13-8-15
20x=-10/:20
x=-1/2
c) 4(x-2)-2(x-4)=5(x+1)-3xbrak znaku ja wstawiłam=
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0≠5

d) 2(x-4)=2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x-4x-6x=-2+6+8
-8x=12/:(-8)
x=12/8
x=1,5
e) 0,2x+0,3=1,3
0,2x=1,3-0,3
0,2x=1/:0,2
x=5
f) 0,2x+0,3=1,3
to samo co e
g) 0,83x+0,82=0,23x+1,52
0,83x-0,23x=1,52-0,82
0,6x=0,7/:0,6
x≈1,166
h) 0,6x+2(0,1x-0,1)=0,2(x+1)
0,6x+0,2x-0,2=0,2x+0,2
0,6x+0,2x-0,2x=0,2-0,2
0,6x=0?0,6
x=0
i) 0,15(2x+4)=2(1,3+0,3x)-0,6
0,3x+0,6=2,6+0,6x-0,6
0,3x-0,6x=2,6-0,6-0,6
-0,3x=1,4/:(-0,3)
x=-4,666
j) 0,1(x+1)-0,05(3x-10)=0,4-0,35x
0,1x+0,1-0,15+0,5=0,4-0,35x
0,1x+0,35x=0,4-0,1+0,15-0,5
0,45x=-0,05/:0,45
x=-0,11111